2012
DOI: 10.3109/0886022x.2012.692752
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Medical Ozone Therapy on Renal Ischemia/Reperfusion Injury

Abstract: Our results clearly showed that OT has beneficial effect to protect kidney against IRI. The serum neopterin levels might be used as a marker to detect the degree of renal IRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
(46 reference statements)
1
12
0
Order By: Relevance
“…In animal models, it had been already demonstrated that ozone therapy could reduce oxidative stress in I/R injury of different organs, such as heart, liver and kidney. [16][17][18] And our in vitro results were in accordance with those of in vivo. We found that kidney cells subjected to H/R caused an elevation of oxidative stress accompanied by increased MDA production and LDH leaking ratio, and reduction in SOD activities.…”
Section: Discussionsupporting
confidence: 87%
“…In animal models, it had been already demonstrated that ozone therapy could reduce oxidative stress in I/R injury of different organs, such as heart, liver and kidney. [16][17][18] And our in vitro results were in accordance with those of in vivo. We found that kidney cells subjected to H/R caused an elevation of oxidative stress accompanied by increased MDA production and LDH leaking ratio, and reduction in SOD activities.…”
Section: Discussionsupporting
confidence: 87%
“…Degeneration in the germinal epithelium, spermatogonia, and spermatids seen in the I/R group was prevented by taurine and/or ozone therapy applications, particularly in the taurine + ozone + I/R group. This protective effect of ozone therapy was previously shown in experimental renal I/R studies (19,20). However, to the best of our knowledge, the present study is the first study about the protective effect of ozone therapy in a testicular I/R model in adult rats.…”
Section: Discussionmentioning
confidence: 35%
“…Other studies have shown that O 3 can activate the antioxidant system, decrease tissue hypoxia, and increase the host immunity and characteristics of microcirculation and general health status of the exposed population (Elvis and Ekta, 2011). The protective properties of non-toxic dose exposure to O 3 on health outcomes including cardiovascular complications, liver injuries, renal injuries, diabetes and its related complications, and radiation induced toxicity have been documented (Delgado-Roche et al, 2013; Ajamieh et al, 2002; Gul et al, 2012; Oztosun et al, 2012; Al-Dalain et al, 2001; Gultekin et al, 2013). However, we can only speculate that our findings reflect negative association of term LBW with O 3 exposure.…”
Section: Discussionmentioning
confidence: 99%